Factors influencing students’ choice to be professionally qualified — an accounting perspective / Melissa Mam Yudi … [et al.] - Yudi, Melissa Mam; Ibrahim, Nurul Nadiah; Kamaruzaman, Siti Aisyah; Haron, Nur Quratun ‘Aini; Sahol Hamid, Nazreen; Hambali, Siti Syaqilah (Faculty of Accountancy, 2019)
Malaysia’s Economic Transformational Programme launched in 2010 as part of Malaysia’s National Transformation Programme, had identified that the country would have to produce 60,000 accountants by year 2020 in an effort to elevate to developed nation status. According to the Malaysian Institute of Accountants (MIA), there are currently 33,000 members registered as at April 2017, which suggests the effort by various governing bodies and institutions must be doubled in order to achieve this target. This paper aims to investigate factors that influence students’ choice in pursuing a professional accounting qualification and the existence of any relationship between demographic factors and their decision to pursue this qualification. For the purpose of this study, focus was on intrinsic motivation, extrinsic motivation and influence of third parties. The sample comprised of 187 male and female students from the only public university in Malaysia offering the professional accounting qualification, ACCA. Questionnaires were distributed to first year students during induction week and analysed using statistical analysis system. The findings indicate that students are mostly driven by intrinsic and extrinsic motivation in their selection to pursue a professional accounting qualification. Findings also demonstrate that there is no relationship between demographic factors and the decision to pursue professional accounting qualification. This research highlights key area upon which universities offering this program and professional accounting bodies should focus and improve to design recruitment strategies. It also fulfils an identified need to study how shortage of professionally qualified accountants in Malaysia should be resolved.